A Canvas of Similes: Unveiling Thematic Richness in Graham Greene's “The Power and The Glory” - Zulfikri, Zulfikri; Mansur, Nurfauziah; Rengur, Zul Aini (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2023)
This research delves into the profound narrative artistry of Graham Greene's